GLUT5-overexpression-related tumorigenic implications - Nikola Hadzi-Petrushev; Radoslav Stojchevski; Anastasija Jakimovska; Mimoza Stamenkovska; Slavica Josifovska; Aleksandar Stamatoski; Iliyana Sazdova; Ramadan Sopi; Andre Kamkin; Hristo Gagov; Mitko Mladenov; Dimiter Avtanski (BMC, 2024)
Abstract Glucose transporter 5 (GLUT5) overexpression has gained increasing attention due to its profound implications for tumorigenesis. This manuscript provides a comprehensive overview of the key findings and implications associated with GLUT5 overexpression in cancer. GLUT5 has been found to be upregulated in various cancer types, leading to alterations in fructose metabolism and enhanced glycolysis, even in the presence of oxygen, a hallmark of cancer cells. This metabolic shift provides cancer cells with an alternative energy source and contributes to their uncontrolled growth and survival. Beyond its metabolic roles, recent research has unveiled additional aspects of GLUT5 in cancer biology. GLUT5 overexpression appears to play a critical role in immune evasion mechanisms, which further worsens tumor progression and complicates therapeutic interventions. This dual role of GLUT5 in both metabolic reprogramming and immune modulation highlights its significance as a potential diagnostic marker and therapeutic target. Understanding the molecular mechanisms driving GLUT5 overexpression is crucial for developing targeted therapeutic strategies that can disrupt the unique vulnerabilities of GLUT5-overexpressing cancer cells. This review emphasizes the complexities surrounding GLUT5's involvement in cancer and underscores the pressing need for continued research to unlock its potential as a diagnostic biomarker and therapeutic target, ultimately improving cancer management and patient outcomes.